Pirates - Nickles, Greg; Nang Chan Yeema (New York, USA Crabtree Publishing Company, 1997)
Presents information about ships, crews, clothing, flags, and life at sea, and suggests games and activities for children.
Keywords: Juvenile Nonfiction